Organoleptic Characteristics of Jerky Analog Made from Young Jackfruit and Tempeh: Sifat Organoleptik Dendeng Analog Berbahan Nangka Muda dan Tempe - Dian P. Prabowo., Ivy; Mahmudi, Mahmudi; Taufiq, Achmad (Universitas Muhammadiyah Sidoarjo, 2023)
Jerky is a meat-based food that is processed by drying to get a longer shelf life. Usually jerky is made from beef. The price of beef which continues to increase every year causes the price of jerky production to also increase. Therefore, it is necessary to make efforts to use foodstuffs that have low prices but are still preferred from an organoleptic point of view. The purpose of this study was to determine the appropriate formulation of the use of young jackfruit and soy tempeh raw materials for the production of jerky analogues which have the most favorable organoleptic properties (taste, texture, aroma, and appearance). The research method was a completely randomized design with four formulas, namely 100% young jackfruit, 80% young jackfruit, 20% tempeh; 60% young jackfruit, 40% tempe; 40% young jackfruit and 60% tempeh. Organoleptic test with an assessment of 1-7 (very very dislike - very very like). The data in this study were analyzed descriptively quantitatively using a t-test analysis with a significance level of 0.05. Proportions of young jackfruit and tempe affect the organoleptic assessment of taste and texture. The best analog jerky formula based on consumer acceptance assessment criteria based on organoleptic is analog jerky using 100% young jackfruit with a taste value of 5.65 (likes-really likes), aroma 5.83 (likes-really likes), texture 5.41 (like - really like), and appearance 5.81 (like - really like).